Melt composition and heat treatment at growth of Gd₂Si₂O₇ — based crystals - Gerasymov, Ia.V.; Sidletskiy, O.Ts.; Baumer, V.N.; Neicheva, S.V. (Functional Materials, 2013)
Paper is devoted to obtaining of scintillation crystals based on gadolinium pyrosilicate Gd₂Si₂O₇. Basic problems of crystal growth and ways of their solving are discussed. Crystals obtained by optimized procedure shows very high efficiency at registration of X-rays.